Perfil tiroideo para el diagnóstico de hipotiroidismo. Laboratorio San Andrés. Saquisilí. mayo 2017- junio 2018. - Ballagán Pilamunga, Johana Estefanía (2018)
hypothyroidism is one of the thyroid illnesses that affects at any stage of life associated with different diseases. the objective of this investigation was to analyze the thyroid profile for the diagnosis of hypothyroidism in the san andrés laboratory during the period from may 2017 to june 2018. the methodology used in this study was descriptive, retrospective, non-experimental, transversal, quantitative approach and inductive-deductive method. the technique used by the laboratory for the determinations of thyrotropin, triiodothyronine and thyroxine was immunofluorescence. the results obtained, establish that 77.5% correspond to the female gender represented by 7.6% of hypothyroid patients, while 22.5% to the male with 1.9% therefore represents 9.5% of the population. also, through the results of tsh, t3 and t4 we obtained individuals with subclinical hypothyroidism with 56% and clinical with 44% within the age groups of 20-54 and 55-87 years.